FACIAL FAT GRAFTING IN THE CORRECTION OF AGE CHANGES - Aleksandruk, Olexandr; Labiak, Ivan; Hutsuliak, Andrii; Prudnikov, Oleksandr; Atamaniuk, Vitaliia (Eastern Ukrainian Medical Journal, 2025)
Introduction. Autologous fat transplantation (lipofilling) holds particular interest as a method for correcting age-related changes in the face due to several unique properties. Firstly, the use of the patient’s own fat ensures maximum biocompatibility and minimizes the risk of allergic reactions. Secondly, adipose tissue contains a significant number of adipose-derived stem cells (ADSC), which have regenerative potential, stimulate angiogenesis, collagen synthesis, and improve skin quality through paracrine mechanisms. Objective. To study the effectiveness of autologous fat transplantation (lipofilling) in correcting age-related changes in the face and neck. Methods. The study included 50 women with involutional changes in the face and neck. The donor site for fat was the inner thigh of the patients. The effectiveness of the procedure was evaluated by ultrasound measurements of skin thickness and subcutaneous fat in the cheekbone and upper cheek areas during three visits: visit 1 – before the procedure, visit 2 – three months after the procedure, and visit 3 – six months after the procedure. Results. Three months after the procedure, skin thickening in the cheekbone area was noted, increasing from 1.73±0.16 mm to 2.08±0.35 mm (>0.05). After six months, a slight, non-significant reduction (>0.05) was observed, although the value remained higher than at visit 1 (1.90±0.38 mm). A similar trend was observed when analyzing the thickness of the skin in the upper cheeks. The thickness of the cheekbone fat pads was significantly higher at visit 2 (9.72±1.02 mm) and visit 3 (9.85±1.16 mm) compared to visit 1 (5.02±0.78 mm). The aesthetic effect of autologous fat transplantation persisted for six months, which can be considered an excellent result. A similar outcome was observed in the analysis of the thickness of the cheek fat pads. Conclusions. Autologous fat transplantation is an effective method for correcting involutional facial changes in middle-aged women, as confirmed by six-month follow-up results in a group of 50 patients. The success of the procedure largely depends on the technical aspects of its performance, including the atraumatic harvesting of fat, proper processing, and injection technique.